From memory to behavior: The role of memorable tourism experiences and destination image in shaping revisit intention through emotions - Nguyen, Tam; Vo, Thuy; Le, Hoa (Journal of Finance - Marketing Research, 2025)
This study investigates the impact of memorable tourism experiences (MTEs) and destination image (DI) on international tourists’ intentions to revisit Ho Chi Minh City (HCMC), with a focus on the mediating effect of post-trip emotional experiences. 27 in-depth interviews were conducted, using the Stimulus-Organism-Response (S-O-R) framework, to investigate how personal memories and emotional connections drive revisit behavior. The results indicate that MTEs and DI do not immediately contribute to revisit intention. Instead, emotions such as a sense of nostalgia, attachment, and the desire to share experiences are recognized as a powerful psychological motivator. Negative emotions, such as annoyance or alienation, on the other hand, reduce the desire to return, even when some encounters are favorable. A notable contribution of this study is its identification of an emotional state that does not shape behavioral intentions, in which visitors maintain meaningful memories but are hesitant to return because of fearing upsetting idealized memories. The study offers practical implications for urban locations, such as Ho Chi Minh City, to promote emotional connections beyond surface attractions, with authentic encounters and ordinary local life serving as strong emotional drivers.